2020
DOI: 10.1097/md.0000000000020749
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dimethylformamide exposure on liver and kidney function in the elderly population

Abstract: Dimethylformamide (DMF) is widely used as a solvent in the production of synthetic leather. Previous studies have focused on workers exposed to DMF in leather factories; however, little attention has been paid to the general population. This study was conducted to examine the effects of DMF exposure on elderly residents living near synthetic leather factories. A total of 962 subjects over 60 years of age in proximity to these factories (monitoring points) were enrolled as the exposure group, and 1924 permanent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…A cross-sectional study examined the effects of DMF exposure in the air on elderly residents living near synthetic leather factories in China. The results showed an increased risk of heart, liver, and kidney injuries associated with DMF exposure [ 38 ]. Methylisocyanate is used in the production of pesticides, polyurethane foam, and plastics and has been detected in cigarette smoke [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study examined the effects of DMF exposure in the air on elderly residents living near synthetic leather factories in China. The results showed an increased risk of heart, liver, and kidney injuries associated with DMF exposure [ 38 ]. Methylisocyanate is used in the production of pesticides, polyurethane foam, and plastics and has been detected in cigarette smoke [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, hydroxyphenyllactic acid, epsilon-caprolactone, allocystathionine, methamphetamine, dimethylformamide, etc., were expressed differently, and the highest fold change reached to as high as 17. Myristoleic acid has been reported to induce apoptotic necrosis of prostate cells ( 16), L-homoserine may be involved in the induction of regulatory T cells (17), and dimethylformamide has been showed to be directly toxic to the kidneys (18). Some studies have been reported that the metabolites in urine may infiltrate into bladder urothelium, related to bladder damage (19).…”
Section: Discussionmentioning
confidence: 99%
“…As the use of DMF has increased year after year, so has concern about its potentially toxic effects. DMF has been shown in animal experiments and epidemiological studies to be toxic to the liver, kidneys, and reproductive system in both humans and animals (7). Previous research has found that the severity of DMF-induced liver injury is directly related to exposure dosage, time of exposure, and the patient's liver function individuals exposed (17).…”
Section: Introductionmentioning
confidence: 99%